2009
DOI: 10.3181/0902-rm-49
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations in the Hypoxia-Inducible Factor-1αGene and Lung Cancer

Abstract: Hypoxia-inducible factor-1 (HIF-1), an important genetic component of angiogenesis, becomes stable as a response to tumor hypoxia and facilitates tumor survival. The polymorphisms of the HIF-1alphagene may cause changes in the activity of this protein, which serves as a transcription factor for many genes in tumorigenesis. In this study, we have investigated the relationship between seven HIF-1alphapolymorphisms [C > T substitution in intron 8 (rs10873142), T418I (rs41508050) in exon 10, P564P (rs41492849), L5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 27 publications
2
13
0
1
Order By: Relevance
“…15,23,24 However, at present, no relationship was evident between HIF-1> polymorphisms and survival in patients with cervical cancer. Hypoxia-inducible factor 1> polymorphisms may not be a prognostic factor of cervical cancer, although we have adjusted the variance of treatments such as radiation therapy, which response was shown to be diminished in cases with overexpression of HIF-1>.…”
Section: Discussionmentioning
confidence: 61%
“…15,23,24 However, at present, no relationship was evident between HIF-1> polymorphisms and survival in patients with cervical cancer. Hypoxia-inducible factor 1> polymorphisms may not be a prognostic factor of cervical cancer, although we have adjusted the variance of treatments such as radiation therapy, which response was shown to be diminished in cases with overexpression of HIF-1>.…”
Section: Discussionmentioning
confidence: 61%
“…Overall,26 relevant studies involving 6337 cases and 9302 controls were selected in this metaanalysis [21,26,27,29,30,32,[43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62]. The main characteristics of these studies were shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Genotype and allele distributions of 1790G/A polymorphism among cancer cases and controls and P value of HWE in controls were shown in Table 1 and 2. All studies were case-control studies, including three oral squamous cell carcinoma (OSCC) studies [46,51,59], three prostate cancer studies [29,44,60], three renal cell carcinoma studies [21,49,57], three breast cancer studies [30,32,50], two gynecologic carcinoma studies [27,53], two colorectal studies [26,62], two pancreatic cancer studies [55,58], three lung cancer studies [47,54,56] and the others(including head and neck squamous cell carcinoma(HNSCC) [43], transitional cell carcinoma of the bladder [45], hepatocellular carcinoma [52], gastric cancer [52], glottic cancer [61]). Cancers were histological or pathological in most studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28,29,30,31,32 İnsanda bulunan üç prolil hidroksilaz izoformu vardır (PHD1-3); normoksik koşullarda HIF-1alfa hidroksilasyonu için öncelikli sorumlunun PHD2 olduğu ileri sürülmüştür. 33,34 HIF-1alfa'nın VHL proteinine bağlanan tarafı oksijen-bağımlı degradasyon (ODD) böl-gesinde bulunur. ODD bölgesi HIF-1alfa'nın amino-terminal transaktivasyon domeyni N-TAD olarak bilinir.…”
Section: Hif-1alfa Ve Vhl Protein Etkileşimiunclassified